2008
DOI: 10.1177/0887403408327384
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Race/Ethnicity on the Perceived Prevalence and Support for Racial Profiling at Airports

Abstract: This article explores citizens' views on racial profiling at airports. A recent Gallup poll allowed for analyses of the perception of Blacks, Hispanics, and Whites concerning whether they felt racial profiling at airports was widespread and/or justified. Multivariate analyses revealed that Blacks were more likely than Whites to believe profiling at airports was widespread. There were, however, no differences between the opinions of Whites and Hispanics on the extent of profiling in airports. Racial and ethnic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…Passengers’ perceptions of airport security measures have not been studied sufficiently, and it is very hard to find a substantive body of research in this area (Gabbidon et al. ; Sindhav et al. ; Lum ).…”
mentioning
confidence: 99%
“…Passengers’ perceptions of airport security measures have not been studied sufficiently, and it is very hard to find a substantive body of research in this area (Gabbidon et al. ; Sindhav et al. ; Lum ).…”
mentioning
confidence: 99%
“…Research shows that men are more supportive of racial/ethnic profiling than women in both the context of preventing crime (Reitzel et al, 2004;Weitzer & Tuch, 2002), and the context of preventing terrorism (Gabbidon et al, 2009). Similarly, conservatives are more approving of racial/ethnic profiling than liberals in both contexts (Gabbidon et al, 2009;Reitzel & Piquero, 2006). Finally, research on New York City residents indicated that education and age were negatively associated with support for profiling in the context of preventing crime (Reitzel & Piquero, 2006, Reitzel et al, 2004.…”
Section: Correlates Of Attitudes Toward Racial/ethnic Profilingmentioning
confidence: 89%
“…Research shows that men are more supportive of racial/ethnic profiling than women in both the context of preventing crime (Reitzel et al, 2004;Weitzer & Tuch, 2002), and the context of preventing terrorism (Gabbidon et al, 2009). Similarly, conservatives are more approving of racial/ethnic profiling than liberals in both contexts (Gabbidon et al, 2009;Reitzel & Piquero, 2006).…”
Section: Correlates Of Attitudes Toward Racial/ethnic Profilingmentioning
confidence: 93%
See 2 more Smart Citations